Adherence to deferasirox among beta-thalassemia major children - A cross-sectional study in a tertiary care hospital - Panda, K; Mishra, N R; Jena, S K (Indian Journal of Child Health, 2018)
Introduction: Deferasirox, an oral iron chelator has been proved to be very safe and effective in beta-thalassemia major children on chronic blood transfusion (CBT); however, adherence to this medication has always been a challenge. Objectives: The aim of this study is to assess the adherence to oral iron chelator- deferasirox among beta-thalassemia major children receiving CBT by using selfreporting questionnaire and the factors associated with poor adherence to deferasirox. Materials and Methods: A cross- sectional study was conducted enrolling 91 beta-thalassemia major children (aged between 2 and 14 years, transfused with at least 20 units of packed red blood cell, on deferasirox therapy and serum ferritin greater than 1000 ng/ml) by simple consecutive sampling. Pretested interview schedule was used to collect information on sociodemographic status. Morisky Medication Adherence Scale was used to measure adherence. Data were entered in Microsoft Excel student 2017 and analyzed using SPSS software version 24. Results: About 7.5% (7) of the patients reported to be highly adherent, 48.4% (45) moderately, and 41.9% (39) were poorly adherent. The mean (SD) serum ferritin value was lowest (1281.71±326.85 ng/ml) in highly adherent children. Association between the age and serum ferritin with adherence to deferasirox done using one-way ANOVA was found to be statistically significant among the three different groups (p=0.000). Illiteracy negatively affected the degree of adherence, while belonging to a nuclear family positively affected the degree of adherence to deferasirox. Conclusion: A very low-adherence level was observed in this study which needs to be improved through adequate measures.